Oral epithelioid hemangioendothelioma - Preeti Tomar Bhattacharya; Mahima V Guledgud; Karthikeya Patil (Wolters Kluwer Medknow Publications, 2015)
Epithelioid hemangioendothelioma (HE) is an intermediate malignant potential vascular neoplasm with uncertain clinical behavior, wide variations in microscopic findings, and prognosis. According to the World Health Organization (2002) classification, epithelioid HE has been considered under malignant tumors which rarely metastasize. The epithelioid variant, the most aggressive one, has similar gender predilection and sporadic occurrence in children. The patients usually present with an asymptomatic oral mass whereas few cases may report with the painful bleeding lesion. We attempt to present a case in an adolescent male with previously never described biological behavior, diverse histopathological features, and immunohistochemistry findings.